PENGGUNAAN TEKNOLOGI VIRTUAL REALITY DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA - Suchy Nadia Putri; Zulfahreza; Sitti Nuralan (Program Studi Teknologi Pendidikan Universitas Madako Tolitoli, 2025)
This study aims to improve student learning outcomes in science learning by using virtual reality technology as a learning medium. The research method used is the Classroom Action Research (CAR) method with the Arikunto model. This research was conducted for 2 cycles, and each cycle consisted of 2 meetings. The subjects of this study were 18 people, namely 17 class VII-b students and 1 science subject teacher of SMP Negeri 4 Tolitoli. The data collection techniques used were observation sheets, test sheets conducted at the end of the cycle and documentation sheets. The results of this study showed that the percentage of classical completeness of class VII-b students in the pre-cycle was 29.42%, after cycle 1 it increased to 58.82% and reached 82.35% after cycle 2. Thus, it can be concluded that the use of virtual reality media in learning can improve student learning outcomes and student activity in the science learning process.